Synthesis and Characteristics of Nickel Doped Barium M-Hexaferrite (BaFe12O19) by Coprecipitation Method - Susilawati, Susilawati; Doyan, Aris; Munib, Munib (Journal of Material Science and Radiation, 2025)
Barium M-hexaferrite (BaFe12O19) as an absorber of microwaves has been synthesized by coprecipitation method and its effect on changes in temperature and dopant substitution. Basic materials used in the synthesis of BaCO3, FeCl3.6H2O and nickel metal. This study used a variation of calcination temperature of 80 ° C, 400 ° C, 600 ° C and 800 ° C for 4 hours with a variety of dopants 0; 0.4; 0.7 and 0.9. The results indicate that the formation of single phase and uniform distribution on M-barium hexaferrite (BaFe12-xNixO19) at 800 ° C calcination temperature and variations in dopant x = 0.7. The elements of barium is spread very evenly matched with the concentration of each element in the compound BaFe12-xNixO19. The addition of the dopant concentration can increase the value of conductivity that is in the range of 10-6 to 10-4 with a coercivity value at x = 0.7 and calcination temperature of 800 ° C at 0.05 T and magnetization value of 2.25 emu /g